2000
DOI: 10.1177/03635465000280021301
|View full text |Cite
|
Sign up to set email alerts
|

A Radiographic and Histologic Evaluation of the Patellar Tendon after Harvesting Its Central Third

Abstract: Nineteen consecutive patients undergoing anterior cruciate ligament reconstruction using the central third of the ipsilateral patellar tendon were included in the study. Serial magnetic resonance images revealed that the donor-site gap in the tendon decreased with time (mean follow-up, 26 months). The thickness was significantly increased compared with the intact contralateral patellar tendon, regardless of when the magnetic resonance imaging was performed. Ultrasonography showed the same findings at a mean fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
88
0
11

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(102 citation statements)
references
References 31 publications
3
88
0
11
Order By: Relevance
“…15,16,21 Other tendinopathic-like features such as mild degenerative changes, 18 increase in cellularity and vascularity, 17 hypoechogeneity, and hyperechogeneity, 15,20,21 increase in tendon width 15,[17][18][19][20]21 as observed with MRI and ultrasonography have also been reported. Bayar et al 15 further described their patients having changes similar to tendinopathy in 6 out of 20 patients.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…15,16,21 Other tendinopathic-like features such as mild degenerative changes, 18 increase in cellularity and vascularity, 17 hypoechogeneity, and hyperechogeneity, 15,20,21 increase in tendon width 15,[17][18][19][20]21 as observed with MRI and ultrasonography have also been reported. Bayar et al 15 further described their patients having changes similar to tendinopathy in 6 out of 20 patients.…”
mentioning
confidence: 91%
“…[8][9][10][11][12] Clinical studies have occasionally reported ectopic calcification after Achilles tendon rupture 13,14 as well as calcification and tendinopathic-like changes in patellar tendon donor site after anterior cruciate ligament (ACL) reconstruction. [15][16][17][18][19][20][21] We hypothesized that chondro-osteogenesis and change in the ECM composition of the repair tissue after acute tendon injury might contribute to the poor tissue quality. This study therefore aimed to examine the presence of chondrocyte phenotype and ossification inside the window wound of the patellar tendon.…”
mentioning
confidence: 99%
“…O processo inflamatório foi classificado em presente ou ausente. A vascularização foi analisada pela classificação apresentada no trabalho de Kartus et al (21) em: grau 0: vasos paralelos às fibras colágenas; grau 1: leve aumento dos vasos; grau 2: moderado aumento dos vasos; e grau 3: acentuado aumento dos vasos.Para a análise estatística considerou-se o grau 0 como normal e os demais foram agrupados, como alterados. Os microsseqüestros ósseos foram avaliados em presentes ou ausentes.…”
unclassified
“…Os microsseqüestros ósseos foram avaliados em presentes ou ausentes. Quanto à celularidade, foi analisada pela classificação descrita nos trabalhos de Kartus et al (21) em: grau 0: até 99 células/ cinco campos; grau 1: 100 a 199 células/ cinco campos; grau 2: 200 a 299 células/ cinco campos; e grau 3: mais de 300 células/ cinco campos.Nesse parâmetro, escolhemos cinco campos aleató-rios para a sua contagem e utilizou-se a contagem total (parâmetro contínuo) para a realização da análise estatística.A avaliação por microscopia óptica foi realizada no Serviço de Anatomia Patológica do Instituto de Ortopedia e Traumatologia do Hospital das Clínicas da Faculdade de Medicina da Universidade de São Paulo. …”
unclassified
See 1 more Smart Citation